Amphotericin B Treatment for Indian Visceral Leishmaniasis: Conventional versus Lipid Formulations - Sundar, Shyam; Mehta, Himanshu; Suresh, A. V.; Singh, Shri P.; Madhukar, Rai; Murray, Henry W. (Clinical infectious diseases, 2004)
In Bihar, India, where visceral leishmaniasis is hyperendemic, amphotericin B deoxycholate is now first-line parenteral treatment. To test the efficacy of amphotericin B deoxycholate versus that of its lipid formulations, Indian patients were randomized to receive treatment with amphotericin B deoxycholate (1 mg/kg on alternate days for 30 days; n = 51), liposomal amphotericin B (2 mg/kg per day for 5 days; n = 51), or amphotericin B lipid complex (2 mg/kg per day for 5 days; n = 51). Infusion-associated reactions were frequent and persistent in subjects treated with amphotericin B deoxycholate. The illness of 3 patients failed to respond to treatment, and 5 patients experienced relapse. Final cure rates were similar. Estimated total treatment costs for a 25-kg patient—$417 for amphotericin B deoxycholate, $872 for liposomal amphotericin B, and $947 for amphotericin B lipid complex—differed as a result of drug cost. Substantial reductions (∼60%) in the price of liposomal amphotericin B and amphotericin B lipid complex would make treatment costs comparable to that of amphotericin B deoxycholate, permitting administration of short-course regimens in India.